Potential of Circular Design in Estonian SMEs and their Capacity to Push it - Vihma, Markus; Moora, Harri (Environmental and Climate Technologies, 2020)
While the capacities of larger enterprises enable them to adopt new circular design approaches and business models, small and medium-sized enterprises (SME) are also increasingly aware of the benefits of closing loops and improving resource efficiency. The SMEs in Estonia are confronted with several obstacles that hinder their circular design related actions. The organizational capacity and capability play a significant role in small businesses when developing concrete solutions for the circular economy, integrate those principles into their strategy and product development process and sustain those efforts. This paper aims to explore the SMEs’ circular design capacity and capability for adopting new approaches in traditional small manufacturing companies who have a product-oriented focus and follow the dominant linear economy business strategy in Estonia. The circular design assessment method was developed to analyse a company’s current status of circularity and evaluate the level of eco/circular design capacity. The results of the study show that the critical dimensions that are crucial for SMEs’ ability to successfully perform circular design are related to their business strategy and planning, owners/manages leadership as well as ability to learn and cooperate and create relationships with external entities for internal dissemination.